Co-application of polyethylene oxide (PEO), biochar, and seaweed fertilizer improves desert soil properties - Haoying Li; Huanan Liu; Bo Qi; Lianghao Zhai; Jiashun Ding; Dan Qiu (Scientific Reports)
Abstract Improving water retention, erosion resistance and nutrients in desert areas is essential for ecological sustainability. This study evaluated the effects of biochar, polyethylene oxide (PEO), and seaweed fertilizer on the properties of desert sandy soil, focusing on water retention, erosion resistance, and soil nutrients. The sandy soil used in the study was taken from the Tengger Desert in Gansu, China, and an orthogonal experimental design was used to select three different proportions of biochar, PEO, and seaweed fertilizer. Compared with the control, applying of these three substances decreased bulk density by 5.8–9.6%, increased porosity by 8.3–14%, and increased water-holding capacity by 2.2–6.7%. The erosion rate decreased by more than 99%, and water-stable aggregates increased by 9.7–37.4%. Soil nutrients showed varying degrees of increase, and seed germination increased by 26.7%. The results of the principal component analysis showed that B6P0.6S2 had the best overall improvement effect. Therefore, a ratio of 6% biochar, 0.6% PEO, and 2% seaweed fertilizer is recommended to improve the properties of sandy desert soils. Overall, biochar, PEO, and seaweed fertilizer can improve the physical properties of desert sandy soil, enhance soil nutrients, and create a stable and suitable environment for plant growth.